Media Desain Berbentuk Promosi SMK Prudent School Tangerang - Vina Vijaya Kusuma; Shella Nurkholisah (UNIVERSITAS RAHARJA, 2019)
Information becomes the keyword of various aspects of life, for this reason it is attention to process. SMK Prudent School needs a poromosi design media to promote SMK Prudent School to prospective students and schoolgirls of SMK Prudent School that will enroll. In this concept, there are results of promotion design SMK Prudent School. In order to produce media design based on good promotion and quality used applications Adobe Photoshop support.